Dr. George Lucas Adamson : founder and first president of Adamson University, Manila : a biography - Adamson, Theresa Juen Di Martile ([Manila, Philippines] : Adamson University, 2012)
George Lucas Adamson, a Greek chemist from Athens, founded the Adamson School of Industrial Chemistry (ASIC) on June 20, 1932 to train young men and women along the lines of practical industrial chemistry.
Chapter 1. Greek History, heritage, Family Greco/Turkish Wat Preparatory School -- Chapter 2. Arrival in the Philippines, Albay, founded ASIC Trip to Japan, USA and Athens Ph. D. Wedding. -- Chapter 3. Intramuros, ASICE Becomes Adamson University -- Chapter 4. Japanese Occupation and Liberation, enemy Alien Prisoners, Family Destruction of Adamson University -- Chapter 5. A new beginning -- Chapter 6. Teamwork Towards Success -- Chapter 7. Looking forward -- Chapter 8 The unification -- Chapter 9. Retirement -- Epilogue. The Last Place in the life story of George Lucas Adamson
Keywords: ADAMSON UNIVERSITY HISTORY